Medical Evacuation from Vietnam of an Elderly with Tuberculosis Spondylitis - Ying-Hua Shieh; Juei-Chin Chang (International Journal of Gerontology, 2007)
Despite the growth in economy in Vietnam, the infrastructure of dependable medical care is still lacking. Therefore, aeromedical evacuation of patients to other countries for further medical interventions has become an important medical service in the region. We report a case where an elderly man who was aeromedically evacuated from Ho Chi Minh City, Vietnam to Taipei Medical University–Municipal Wan Fang Hospital in Taipei, Taiwan. The patient developed a sudden onset of quadriplegia because of an epidural abscess at the cervical spine C6–C7. Antituberculous medication was prescribed for suspected tuberculous spondylitis, because his cerebral spinal fluid showed elevated white blood cells with a predominance of lymphocytes, and mildly elevated total protein. However, whole body tumor scan (67Ga mCi) and whole body bone scan (99mTc methylene diphosphonate, 25 mCi) did not reveal any specific results. Surgical intervention was arranged because of cervical spine instability and the need for a diagnostic biopsy. Adenocarcinoma of the prostate was found incidentally and was treated with bilateral orchiectomy and radiation therapy. This was the first medical evacuation by the Family Medical Practice group in Ho Chi Minh City, Vietnam to Taiwan.